ANALISIS KUALITAS KOMIK ETNOSAINS LITERASI TEMA INDAHNYA KEBERSAMAAN UNTUK SISWA SEKOLAH DASAR - Galuh Rahayuni; Aris Naeni Dwiyanti; Gigih Winandika (Program Studi Pendidikan Guru Sekolah Dasar STKIP Al Hikmah Surabaya, 2020)
Comics are a form of cartoon that expresses characters amd factd out a tory in a sequence that is closely related to images and is designed to images and is designet to provide entertainment to the reader. According to research on 5000 students form 50 schools i n Jakarta, 86% of them like comics. in comics, studnets can not only read but also enjoy the illustrations in the story. based on this, the researcher thiks that if the subject matter is presented in comic form, the matterial will be aesily absorbed because the subject matter is made in the form of story and presented attractively with additional pictures. The aim of the research is to know the quality of comic based on media, linguist, and learning material expert. This research is descriptive research with review report of Penelitian Dosen Pemula (PDP). Subject in this research are media, linguist, and learning material expert. Based on the research subject, the data was collected by distributing a questionnaire to each expert. The questionnaire sheet in this research was used to determine the quality of the comics developed. From the research result it can be concluded that 71% of comic quality is very good from media expert, 33% of comic quality is very good from linguist expert, and 100% of comic quality is very good from learning material expert.